AI-Enhanced Innovation Ambidexterity: The Role of IC, DC, and Innovation Orientation in the Pharmaceutical Industry - Gameel, Zeanab Abdullah Ahmed; Elshamly, Amina (Migration Letters, 2023)
Dynamic challenges and opportunities mark the global pharmaceutical industry, necessitating firms to effectively balance innovation ambidexterity—simultaneously exploring new opportunities while exploiting existing resources. This study investigates the complex interplay of Intellectual Capital (IC), Dynamic Capabilities (DC), and innovation orientation (IO) in driving innovation ambidexterity in the Egyptian pharmaceutical industry. A quantitative methodology was utilised, collecting data via a questionnaire survey administered to experts working in the pharmaceutical industry. The study generated and evaluated hypotheses to investigate the links between IC, DC, innovation ambidexterity, and the moderating effect of IO. The findings reveal that IC significantly influences innovation ambidexterity, highlighting the critical role of knowledge resources. DC mediate the relationship between IC and innovation ambidexterity, emphasising the importance of a firm’s capacity to sense and seize opportunities. Furthermore, IO moderates the relationship between IC and innovation ambidexterity, showcasing the contextual relevance of firms’ innovation focus. This study contributes to our understanding of innovation ambidexterity in the pharmaceutical industry and underscores the importance of IC in fostering this capability. Firms are encouraged to invest in IC and cultivate DC to successfully navigate the evolving pharmaceutical landscape. The moderating effect of IO suggests the need for tailored strategies based on firms’ specific contexts. The implications of this research extend to organisations striving to achieve innovation ambidexterity in dynamic industries.